1979
DOI: 10.1038/ki.1979.70
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of vascular lesions in acute renal failure with microangiopathic hemolytic anemia (hemolytic-uremic syndrome): Clinicopathologic study in 20 adults

Abstract: Renal biopsies obtained from 20 adult patients within 30 days after onset of acute renal failure with microangiopathic hemolytic anemia ("the hemolytic-uremic syndrome") were studied. Lesions were graded independently by two observers without knowledge of the clinical history. All patients who did not have refractory hypertension were treated with heparin. Ten of the patients died, and four developed end-stage renal failure requiring chronic dialysis. Six patients, however, had a relatively good outcome: two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
1
2

Year Published

1981
1981
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(44 citation statements)
references
References 19 publications
4
37
1
2
Order By: Relevance
“…This may partly explain the low prevalence of microangiopathic hemolytic anemia in these patients. Morel-Maroger et al (15) disclosed that microangiopathic hemolytic anemia may occur in apparently healthy people, or may complicate the course of chronic essential hypertension. The patients with a good outcome and those with a poor outcome did not differ in the severity of glomerular lesions but did differ in the severity of arterial intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…This may partly explain the low prevalence of microangiopathic hemolytic anemia in these patients. Morel-Maroger et al (15) disclosed that microangiopathic hemolytic anemia may occur in apparently healthy people, or may complicate the course of chronic essential hypertension. The patients with a good outcome and those with a poor outcome did not differ in the severity of glomerular lesions but did differ in the severity of arterial intimal thickening.…”
Section: Discussionmentioning
confidence: 99%
“…12,28,31 Distinguishing between these patterns of involvement has some prognostic value. 24 The ultrastructural lesions in Greyhounds with CRGV also most closely resemble those of the childhood variant of HUS.9JoJ6,33,3s In Greyhounds with CRGV and children with HUS, lesions are predominately glomerular and include marked reduction of the capillary lumina due to expansion of the subendothelia1 space by flocculent material; occlusion of the cap-illaries by aggregates of platelets, erythrocytes, fibrin, and cellular fragments; endothelial swelling, hypertrophy, and villous cytoplasmic projections; and interposition of mesangial cytoplasmic processes within the subendothelial space.…”
Section: Discussionmentioning
confidence: 99%
“…13,[68][69][70] However, the effectiveness of the use of plasma in the treatment of acute episodes is still controversial. 71 Some studies have shown that a consistent percentage of patients with atypical HUS respond to treatment with plasma.…”
Section: Treatment For Atypical Husmentioning
confidence: 99%